Gestational Diabetes Mellitus and Associated Risk Factors in Patients Attending Diabetic Association Medical College Hospital in Faridpur (Journal of Enam Medical College, 2017)
Background: The prevalence of gestational diabetes mellitus (GDM) is increasing all over the world and varies widely depending on the region of the country, dietary habits and socio-economic status. The prevalence of GDM with its associated risk factors has important health complications for both mother and child.Objectives: The aim of this study was to evaluate the prevalence of GDM and risk factors associated with it in women attending Diabetic Association Medical College Hospital in Faridpur for ante-natal care.Materials and Methods: In this cross-sectional study, screening for GDM was performed in 303 pregnant women. Women who consented to participate underwent a standardized 2-hour 75 gm oral glucose tolerance test (OGTT). A proforma containing general information on demographic characteristics, socio-economic status, education level, parity, family history of diabetes and past history of GDM etc. was filled in. American Diabetes Association (ADA) criteria for 75 gm 2-hour OGTT was used for diagnosing GDM.Results: A total of 303 women participated in the study and GDM was diagnosed in 22 (7.3%) women. A single abnormal value was observed in additional 33 (10.89%) women. On bivariate analysis risk factors found to be significantly associated with GDM were age, household income, parity, educational level, socio-economic status, hypertension, BMI, weight gain, acanthosis nigricans, family history of diabetes and past history of GDM; but on multivariate analysis only upper middle class and presence of acanthosis nigricans were found to be significantly associated with GDM.Conclusion: This study demonstrates a high prevalence of GDM in Bangladesh. These estimates for GDM may help for new suggestions to prevent and manage gestational diabetes.J Enam Med Col 2017; 7(3): 126-133